Sources of sustainable competitive advantage: the case of rice-milling firms in Thailand. Issue 2 (25th February 2014) - Ritthaisong, Yuttakorn; M. Johri, Lalit; Speece, Mark
Abstract : Purpose: – This paper aims to investigate the effect of several valuable resources (organizational reputation, human resource management (HRM) practices, networks, and vertical integration in production) in explaining the performance of rice-milling firms in Thailand. Design/methodology/approach: – Resource-based view (RBV) theory was used to explain that the particular bundle of firm resources can become the source of sustainable competitive advantage and thereby improve the business's performance. Semi-structured in-depth interviews and questionnaire were used to collect data from Thailand rice exporters. Then regression technique was employed for data analysis. Findings: – Results from a survey of rice mills involved in international export showed that organizational reputation, some HRM practices, and networks were significantly related to firm's performance, but vertical integration was not. Originality/value: – This study supports the basic assertion of RBV theory that a set of firm specific resources could be applied in ways that enhance sustainable competitive advantage.